The Work of Art in a Digital Age: Art, Technology and Globalisation - Langdon, Melissa (Springer New York : Imprint: Springer, 2014)
This book explores digital artists' articulations of globalization. Digital artworks from around the world are examined in terms of how they both express and simulate globalization's impacts through immersive, participatory and interactive technologies. The author highlights some of the problems with macro and categorical approaches to the study of globalization and presents new ways of seeing the phenomenon as a series of processes and flows that are individually experienced and expressed. Instead of providing a macro analysis of large-scale political and economic processes, the book offers imaginative new ways of knowing and understanding globalization as a series of micro affects. Digital art is explored in terms of how it re-centers articulations of globalization around individual experiences and offers new ways of accessing a complex topic often expressed in general and intangible terms. The Work of Art in a Digital Age: Art, Technology and Globalization is analytic and accessible, with material that is of interest to a range of researchers from different disciplines. Students studying digital art, film, globalization, cultural studies or digital media trends will also find the content fascinating.